THE FEASIBILITY OF IMPROVING CONCRETE STRENGTH PROPERTIES BY ADDING WASTE WOOD CHIPS - Sharba, Amjad Ali Khudheyer; Al-kaabi , Jasim Jarallah Fahad; Al-Taai, Salwa R. (Journal of Applied Engineering Science, 2023)
This paper examines the ability to introduce an industrial waste product, wood chips, in concrete as a partial replacement for fine aggregate. Water was used to treat the wood chips before mixing to prevent them from soaking up the cement hydration water. The research presented in this paper aims to determine the impact of different treatment methods. The first method uses cement paste, and the second is sodium silicate. Twelve trial mixtures were prepared and cast employing water-cement ratios of 0.44 at various replacement levels of wood chippings. Fresh concrete properties tested inclusive slump test. Hardened concrete properties tested inclusively flexural strength, splitting tensile strength, compressive strength, and unit weight. Test results show that the lightening of concrete by wood shavings decreases the strength properties and the unit weight. On the other hand, the value of the slump test increased depending on the level of replacement of wood shaving. The most acceptable mixture and less reduction in the strength properties have been shown at MC10. The results of the tests demonstrate that the disposal of wood chips in concrete is practical and appropriate.
Keywords: wood chipping, composite material, treatment, mechanical strength